Effect of Acrylamide and Potassium Persulfate on The Characteristics of Water Hyacinth-Carrageenan Bead Gel Using Microwave Grafting Method - Distantina, Sperisa; Putra, Novan Aldian Rahmadan; Naryani, Rahma Fitri; Kaavessina, Mujtahid (Universitas Ahmad Dahlan, 2023)
The cellulose of water hyacinth (Eichhornia crassipes) was utilized as raw material in bead gel production. In this research, hydrogel was prepared by grafting of acrylamide (AA) monomers onto the water hyacinth cellulose as the backbone using the microwave to produce hydrogel. This research aimed to determine the influence of adding AA and potassium persulfate (PPS) as an initiator on characteristic of swelling capacity in water. The cellulose powder obtained from the stem of water hyacinth was immersed in NaOH solution (1.5 N) for the delignification process for 10 min. The resulted cellulose was mixed with water and varying additions of 4, 7, dan 10 g acrylamide (AA) and 0.05, 0.10, and 0.15 g PPS to undergo grafting reaction. The obtained gel was washed and soaked in the acetone to remove the unreacted AA and PPS. The resulting precipitated solid was dried and called Water Hyacinth Cellulose Grafted Polyacrylamide (WH cellulose-g-PAA). The mixture of carrageenan with WH cellulose-g-PAA underwent crosslinking using aqueous KCl and CaCl2 after passing through palm oil layer to form bead gel. The properties of the dried bead gel were tested for functional groups using FTIR and for swelling capacity in water. Based on the FTIR test results, it can be concluded that AA monomers were successfully grafted onto the water hyacinth cellulose backbone. The addition of AA that is too low or too high will reduce the swelling capacity, as well as PPS.